2015
DOI: 10.1007/s00253-015-6433-4
|View full text |Cite
|
Sign up to set email alerts
|

Dirhamnose-lipid production by recombinant nonpathogenic bacterium Pseudomonas chlororaphis

Abstract: We previously discovered that Pseudomonas chlororaphis NRRL B-30761 produces monorhamnolipids (R1Ls) with predominantly 3-hydroxydodecenoyl-3-hydroxydecanoate (C12:1-C10) or 3-hydroxydodecanoyl-3-hydroxydecanoate (C12-C10) as the lipid moiety under static growth conditions only. We have now cloned, sequenced, and analyzed in silico the gene locus of NRRL B-30761 containing the putative coding sequences of rhamnosyltransferase chain A (rhlA Pch , 894 bps), rhamnosyltransferase chain B (rhlB Pch , 1272 bps), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Finally, we included the rhlA from P. fluorescens LMG 05825 (P. chlororaphis ATCC 17813), which is reported to be the same strain as P. chlororaphis NRRL B-30761 (35), a strain producing mainly C 10 -C 12 and C 10 -C 12:1 congeners (15). Solaiman et al (36) found an operon containing rhlAB and the regulator gene rhlR (Fig. 3) in this strain.…”
Section: Figsupporting
confidence: 54%
See 1 more Smart Citation
“…Finally, we included the rhlA from P. fluorescens LMG 05825 (P. chlororaphis ATCC 17813), which is reported to be the same strain as P. chlororaphis NRRL B-30761 (35), a strain producing mainly C 10 -C 12 and C 10 -C 12:1 congeners (15). Solaiman et al (36) found an operon containing rhlAB and the regulator gene rhlR (Fig. 3) in this strain.…”
Section: Figsupporting
confidence: 54%
“…the C 12 chain is unsaturated in one position (15,35,36). In contrast, Burkholderia kururiensis KP23 produces Gammaproteobacteria-like rhamnolipids containing mainly C 10 -C 10 residues (24).…”
mentioning
confidence: 99%
“…The authors reported that the modified P. chlororaphis was able to produce 2.4 fold more dirhamnolipids than mono-rhamnolipids [76]. A previous study of the same group reported that a 3-hydroxyacyl-ACP/CoA transacylase (phaG)-knockout does not affect rhamnolipid synthesis [77].…”
Section: P Aeruginosa Genes In Heterologous Hostsmentioning
confidence: 96%
“…In these ways, a modified P. chlororaphis strain was also designed, harboring plasmid pBS29-P2-rhlC, and expressing of the rhamnosyltransferase C (rhlC) gene from P. aeruginosa, under control of a Pseudomonas syringae promoter [76]. The authors reported that the modified P. chlororaphis was able to produce 2.4 fold more dirhamnolipids than mono-rhamnolipids [76].…”
Section: P Aeruginosa Genes In Heterologous Hostsmentioning
confidence: 98%
“…and Burkholderia sp., implying that the metabolic engineering can also provide a means in modifying the composition and types of rhamnolipid congeners produced to alter the physicochemical properties of the rhamnolipids [ 48 ]. Likewise, P. chlororaphis, which was previously reported to produce only mono-rhamnolipids, was shown to be able to produce di-rhamnolipids by overexpressing rhlC under a constitutive promoter [ 49 ]. The rhamnolipid composition was also altered by site-directed mutagenesis on rhlB that resulted in the modification to the volume of the substrate binding pocket [ 50 ].…”
Section: Application Of Various Strategies To Increase Rhamnolipid Yimentioning
confidence: 99%